Odinala Traditional Religion as Part of Igbo Catholic Christian Identity - Ondřej Havelka (Communio Viatorum)
Although recent statistics indicate that the majority of the Igbo – an ethnic group living mainly in West African Nigeria – claim to be Christian (of various denominations), their religious identity is in fact more complex: the Igbo do not forget their traditional Odinala religion and practice it together with Christianity without intermingling (multiple religious identity) or in syncretism with Christianity. Odinala is, in short, a polytheistic religious system where the highest reverence belongs to the god Chukwu. The aim of this article is firstly to give an introduction to the traditional Igbo religion of Odinala and secondly its influence on the co-formation of the identity of the Igbo – we choose for the purpose of this article – Catholic Christian. Through the ontological categories of Odinala religion, the paper examines how Odinala shapes the Igbo worldview, how it co-constitutes Igbo identity and helps to establish the ontological category of the human person. The topic is developed through a field research method, reinforced by a comparison of relevant literature.